Plasma Lyso-PE 22:6 and Lyso-PE 20:4 are associated with development of mild to moderate depression revealed by metabolomics: a pilot study - Jingbo Yu; Haixia He; Xianyang Chen; Yue Han; Yige Song; Lei Wang; Hongqing Zhao; Yuhong Wang (BMC Psychiatry)
Abstract Background Mild to moderate depression (MMD), as an early stage of depression, has a high incidence and may progress to severe depression, even leading to suicide. The lack of effective screening and treatment is due to the unknown metabolic changes and processes in patients with MMD. Here, we performed metabolite profiling to investigate the key metabolites associated with MMD in plasma. Methods A high-throughput metabolomics method using ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS) was used to determine the metabolic profiles of patients with MMD. Metabolic network analysis and machine learning models were used to screen and assess potential biomarkers of MMD. Results Forty altered metabolites were identified between patients with MMD and healthy controls, which were mainly involved in seven metabolic pathways associated with amino acid and lipid metabolism. A metabolite-target-disease network was constructed to screen six metabolites as potential key metabolites most relevant to the onset of depression. Furthermore, 12 of the 40 metabolites were found to have a strong linear correlation with scores on the Hamilton depression scale. By combining network analysis with linear correlation, we identified lysophosphatidylethanolamine (Lyso-PE) 22:6 and Lyso-PE 20:4 as being associated with the development of depression. These two metabolites showed potential in distinguishing patients with MMD from healthy controls and exhibited different correlations with other key metabolites. Conclusion Our findings suggest that Lyso-PE 22:6 and Lyso-PE 20:4 are associated with the development of depression, indicating their potential use in future screening applications to prevent the progression of depression. Graphical abstract